Village Level Labor Market Development in Tanzania : Evidence from Spatial Econometrics - John K. Mduma; Peter Wobst (University of Bonn, Center for Development Research (ZEF), 2005)
While many empirical studies show that participation in rural labor markets is an important household livelihood strategy, data on Tanzania show that the participation in the rural labor markets is still relatively low. This study examines the factors behind the development of village labor markets in Tanzania. Using spatial econometric techniques, the study shows that, despite their incipient development, rural labor markets in Tanzania are significantly interlinked across space. Furthermore, underlying factors for development of rural labor markets, such as access to roads and availability of credit, have varying impacts across space. This implies that policy interventions such as making credit available to the rural households and investment in rural transport infrastructure would also have varying effects across space. The study reveals that interventions that reduce cash constraints such as rural credit schemes are likely to have greater impacts in the western part of the country than in the eastern part. However, interventions that reduce the time used in collecting firewood are likely to have more pronounced impacts in the eastern parts than in the western parts of the country. While east-west variations of most of these interventions are significant, most of the north-south variations are not significant. This phenomenon is partly attributed to east-west alignment of key infrastructure such as transport networks. – – Während viele empirische Studien zeigen, dass die Partizipation in ländlichen Arbeitsmärkten eine wichtige Strategie zur Sicherung des Lebensunterhalts von Haushalten ist, ist die entsprechende Partizipation im Falle Tansanias immer noch verhältnismäßig gering. Diese Studie untersucht die für die Entwicklung der dörflichen Arbeitsmärkte in Tansania ausschlaggebenden Faktoren. Mittels räumlich-ökonometrischer Methoden, zeigt diese Studie, dass die ländlichen Arbeitsmärkte in Tansania?trotz ihrer bisher mässigen Entwicklung?stark räumlich Beziehungen aufweisen. Desweiteren haben die der Entwicklung der ländlichen Arbeitsmärkte zugrundeliegenden Faktoren, wie etwa der Zugang zu Transportwegen oder Krediten, sehr unterschiedliche rämliche/regionale Auswirkungen. Daraus ergibt sich, dass staatliche Maßnahmen wie etwa die Bereitstellung ländlicher Kredite oder Investitionen in ländliche Transportinfrastruktur ebenfalls sehr unterschiedliche räumliche/regionale Effekte haben. Die Studie verdeutlich, dass etwa Maßnahmen, die die Liquidität von Farmern erhöhen, wie etwa die Einführung eines ländlichen Kreditsystems, einen größeren Effekt auf den westlichen Teil des Landes hätten als auf den östlichen. Andererseits würden Interventionen, die zu einer Reduzierung der Zeit, die für das Sammeln von Feuerholz verwendet wird, führen, voraussichtlich stärker dem östlichen als dem westlichen Landesteil zugute kommen. Während die Ost-West-Abweichungen der meisten Interventionen signifikante sind, besteht keine eindeutige Nord-Süd-Abweichung. Dieses Phänomen ist zum Teil der Ost-West-Ausrichtung der bestehenden Infrastruktur, wie etwa dem Transportnetz zuzuschreiben.
Keywords: 330; Ländlicher Arbeitsmarkt; Dorf; Regionale Entwicklung; Räumliche Interaktion; Schätzung; Tansania